2021
DOI: 10.32479/ijeep.11075
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption-Poverty Reduction Nexus in Brics Nations

Abstract: This study investigated the impact of energy consumption on poverty in BRICS using panel data analysis methods (fixed effects, pooled OLS, random effects, FMOLS) with annual data ranging from 1995 to 2018. Whether economic growth is a channel through which energy consumption influences poverty in BRICS was also a subject of investigation in this study? Although there is acknowledgment that energy consumption reduces poverty through economic growth by authors such as Okwanya et al ( 2015), Hussein and Filho (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The empirical results reveal that energy consumption and per capita are significant and negatively associated with poverty in both short- and long-run as illustrated in the models A and B. These outcomes are similar to the findings of Hussein and Filho (2012), Kunofiwa (2021), Nkomo (2017), Ogbeide and Evelyn (2020) and Sakanko and David (2018) in the literature. Moreover, the significant and inverse relationship between income and poverty are also congruent with the previous studies (Ali and Sharif, 2020; Janjua and Kamal, 2011; Satti et al, 2015; Tombolotutu et al, 2018).…”
Section: Ardl Test Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The empirical results reveal that energy consumption and per capita are significant and negatively associated with poverty in both short- and long-run as illustrated in the models A and B. These outcomes are similar to the findings of Hussein and Filho (2012), Kunofiwa (2021), Nkomo (2017), Ogbeide and Evelyn (2020) and Sakanko and David (2018) in the literature. Moreover, the significant and inverse relationship between income and poverty are also congruent with the previous studies (Ali and Sharif, 2020; Janjua and Kamal, 2011; Satti et al, 2015; Tombolotutu et al, 2018).…”
Section: Ardl Test Resultssupporting
confidence: 84%
“…They established that in order to maintain the positive effect of energy consumption on poverty reduction; quality infrastructure and political stability in the nation play a crucial role. On contrary, the study of Kunofiwa's (2021) found a considerable (negative) influence of energy use in combatting poverty, and it was suggested to implement such policies that assure increased energy consumption geared toward poverty reduction in Brazil, Russia, India, China, and South Africa (BRICS) nations. In light of the aforementioned discussion, we hypothesize that H1.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Such results mean that the data for most variables do not follow a nor-mal distribution, consistent with Tsaurai (2021). Following Tsaurai (2020), this study addressed the econometrics problems (data not following a normal distribution pattern, extreme values, multi-collinearity problem) using natural logarithm data for the main data analysis. This study used Levin, Lin, and Chu (2002), Phillips-Perron-Fisher Chi-Square, Im, Pesaran, and Shin (2003), and the Augmented Dickey-Fuller-Fisher Chi-Square tests as approaches for testing the existence of stationarity.…”
Section: Pre-estimation Diagnosticsmentioning
confidence: 99%
“…The finance–poverty relationship has been examined by Tsaurai (2020) in the BRICS (Brazil, Russia, India, China, and South Africa) using the fully modified ordinary least squares (FMOLS), fixed effects, and pooled ordinary least squares (POLS) regressions for the period 1994 and 2013. The findings reveal that poverty reduction is jointly affected by foreign direct investment (FDI) and financial development.…”
Section: Literature Reviewmentioning
confidence: 99%